Renal Development and Neonatal Adaptation - Saint-Faust, M.; Boubred, F.; Simeoni, U. (American Journal of Perinatology, 2014)
The structural and functional development of the kidney is responsible for a significant impact on postnatal adaptation to extrauterine life. Prenatal or neonatal impairment of nephrogenesis may carry long term, lifelong consequences in terms of reduced nephron endowment, chronic kidney disease, and cardiovascular risks at adulthood. Intrauterine growth restriction, preterm birth, congenital renal, and urinary tract anomalies are for long widely incriminated. Neonatal administration of nephrotoxic drugs has been associated with short-term acute kidney injury and longer chronic kidney disease. This review attempts at offering a comprehensive understanding of the renal development, the neonatal renal transition to extrauterine life and subsequent maturation phase during early infancy. It also focuses on developmental and maturational changes that impact lifelong renal function and adult health.
Keywords: renal development; neonatal adaptation; intrauterine growth restriction; drugs toxicity